UVA irradiation of riboflavin generates oxygen-dependent hydroxyl radicals. (March 2014) - Sel, Saadettin; Nass, Norbert; Pötzsch, Sandy; Trau, Stefanie; Simm, Andreas; Kalinski, Thomas; Duncker, Gernot IW.; Kruse, Friedrich E.; Auffarth, Gerd U.; Brömme, Hans-Jürgen
Abstract : Objectives/methods: The aim of this study was to verify the formation of hydroxyl radicals (·OH) after ultraviolet A (UVA) irradiation of riboflavin (RF) by spin trapping with 5, 5-dimethyl-1-pyrroline- N -oxide (DMPO), and electron spin resonance spectroscopy. Results: We found that ·OH were generated via hydrogen peroxide (H2 O2 ) formation during UVA irradiation of RF. The ·OH radicals were trapped with DMPO yielding 2-hydroxy-5, 5-dimethyl-1-pyrroline- N -oxide (·DMPO-OH). The formed radical adduct (·DMPO-OH) accumulated in the RF solution. Argon equilibration of the RF solution completely blocked the formation of the ·DMPO-OH adduct whereas subsequent aeration restored radical adduct generation. The presence of catalase inhibited ·DMPO-OH generation whereas BSA had no influence on ·DMPO-OH formation. Stopping UVA irradiation led to decay of radical adducts. UVA irradiation of H2 O2 in the presence of DMPO but without RF also induced the formation of ·DMPO-OH adduct. When adding DMPO to an already irradiated RF solution significantly less ·DMPO-OH was formed during further irradiation. Ultraviolet-visible spectroscopy and high-performance liquid chromatography analysis of RF indicated that RF decayed during UVA irradiation. Discussion: The formation of ·OH during UVA irradiation of RF may be part of the oxygen-dependent mechanism involved in the cross-linking therapy of collagen in corneal stroma.